Effects of COVID-19 on Sustainable Development Goal 3 in Sub-Saharan Africa - Gladys, Mangwanya Maonei; Emmanuel, Uwizeyimana Dominique (Penerbit Universiti Kebangsaan Malaysia, 2023)
Achieving the Sustainable Development Goals has been a considerable challenge in Africa, especially with the advent of the COVID-19 pandemic. Africa has been struggling to deal with the repercussions of the pandemic as well as other deadly diseases such as tuberculosis, malaria, diabetes, and HIV, which are widespread in all African countries. The purpose of this paper was to assess the impact of COVID-19 on the vulnerable healthcare system on the African continent. The study's primary objective is to explore the impact of COVID-19 on achieving Sustainable Development 3 (Good Health and Well Being). The paper reviewed literature on health-related issues and the effects of COVID-19, including mortality rates, and correlates the findings to the Goal Setting Theory. The study utilised a qualitative research design, with the researchers using secondary data to understand how the pandemic has jeopardised the accomplishment of good health and well-being. The conclusions of the researchers were based on numerous organisation reports, scholarly articles, media articles, and internet sources. The data was evaluated using a thematic technique with all findings organised into themes. Given the negative impact of the pandemic, the researchers gave recommendations towards the African Healthcare System.